374 The effects of a yeast fermentation product on diet palatability, apparent total tract macronutrient digestibility and fecal characteristics of adult dogs. - Lin, C (J Anim Sci, 2018)
The objective of this study was to investigate the effects of a yeast fermentation product on diet palatability, apparent total tract macronutrient digestibility, and fecal characteristics of adult dogs. Twelve adult female beagles (age: 3.3 ± 0.8 yr, BW: 10.3 ± 0.68 kg) were fed the same diet, but supplemented with a yeast fermentation product at 3 dosages (125, 250 or 500 mg/d) or a placebo (125 mg sucrose/d) via gelatin capsules in a replicated 4 x 4 Latin square design. In each period, a 21-d adaptation phase was followed by 5 d of total fecal collection for apparent total tract macronutrient digestibility measurement. Fresh fecal samples were collected for pH, fermentative end-products, and fecal microbiota measurement. A separate palatability study using a two-bowl test compared a control diet (no yeast) vs. yeast-containing diet (0.2%; comparable to the 500 mg/d dose). Data were analyzed using SAS 9.4. A 1.9:1 consumption ratio for yeast-containing vs. control diet was observed, demonstrating a preference (p<0.05) for yeast product. Dog BW and BCS were maintained throughout the study. Apparent total tract macronutrient digestibilities and fecal characteristics, including pH, fecal score and wet fecal output were not altered by treatment when each was analyzed against one another individually. However, fecal score was slightly increased (looser stools) linearly (p<0.05) with increasing yeast supplementation. All fecal metabolites, except for phenol were not affected by treatment. Dogs supplemented with 500 mg yeast product had lower (p<0.05) fecal phenol concentrations than control dogs, with dogs supplemented with 125 mg or 250 mg yeast product being intermediate. Fecal phenol and total fecal phenol + indole concentrations were decreased (p<0.05) linearly with increasing yeast dosages. In conclusion, the yeast fermentation product increased diet palatability, decreased fecal phenol concentration, and increased fecal score.